Evaluation, management and prevention of lower extremity youth ice hockey injuries - Popkin, C. A.; Schulz, B. M.; Park, C. N.; Bottiglieri, T. S.; Lynch, T. S. (Open Access Journal of Sports Medicine, 2016)
Ice hockey is a fast-paced sport played by increasing numbers of children and adolescents in North America and around the world. Requiring a unique blend of skill, finesse, power and teamwork, ice hockey can become a lifelong recreational activity. Despite the rising popularity of the sport, there is ongoing concern about the high frequency of musculoskeletal injury associated with participation in ice hockey. Injury rates in ice hockey are among the highest in all competitive sports. Numerous research studies have been implemented to better understand the risks of injury. As a result, rule changes were adopted by the USA Hockey and Hockey Canada to raise the minimum age at which body checking is permitted to 13-14 years (Bantam level) from 11-12 years (Pee Wee). Continuing the education of coaches, parents and players on rules of safe play, and emphasizing the standards for proper equipment use are other strategies being implemented to make the game safer to play. The objective of this article was to review the evaluation, management and prevention of common lower extremity youth hockey injuries.